Elevated concentrations of quaternary ammonium compounds in childcare centers: A pilot study - Yao Cheng; Zhong Lv; Erika Schreder; Min Hu; Abby Mutic; Guomao Zheng; Amina Salamova (Journal of Hazardous Materials Letters)
Quaternary ammonium compounds (QACs) are used as antimicrobials, preservatives, and antistatic agents in cleaning, disinfecting and personal care products, and textiles. High levels of QACs have been found in indoor dust in residential homes; however, there is limited information on QAC exposure in non-residential environments serving sensitive populations, such as childcare centers. In this study, we investigated the occurrence of QACs, including benzylalkyldimethyl ammonium compounds (BACs), dialkyldimethylammonium compounds (DADMACs), and alkyltrimethylammonium compounds (ATMACs), in dust from childcare centers and estimated daily intake of QACs by toddlers in chidlcare via dust ingestion. Nineteen QACs were detected in dust with a median total QAC concentration (ΣQAC) of 150 μg/g. BACs were the most abundant QAC group found at concentrations ranging from 2.67 to 1370 μg/g (median 90.4 μg/g) and constituted 64 % of the ΣQAC concentrations. The QAC levels in dust from childcare centers were significantly higher than concentrations previosly reported in homes. The EDIs for BACs, DADMACs, and ATMACs via dust ingestion calculated based on the 95th percentile concentrations in childcare dust were up to 30 times higher than those for toddlers in residential homes. These findings demonstrate high QAC exposure in childcares, posing significant early-life exposure for toddlers.